MEMPERTIMBANGKAN KUALITAS DATA KUALITATIF WAWANCARA PADA PARTISIPAN YANG MENGALAMI KESULITAN DALAM MENJELASKAN PENGALAMAN SECARA DETAIL - Musdalifah Dachrud (Institut Agama Islam Negeri (IAIN) Manado, 2015)
This paper discusses the constraints and challenges that may arise when conducting qualitative interviews with people with language disabilities or the weak elderly who have difficulty explaining in detail about their experiences. The literature on qualitative research seems to assume that good quality qualitative interviews consist of long and unbroken narratives. This ideal includes specific requirements for research participants. Qualitative studies including weak elderly people or people with disabilities in communication will be disadvantaged by biased samples or vague descriptions. Strategies to maximize the quality of interview data, such as larger samples and more varied samples, require an investment of sufficient time to build a